Gestión de riesgo de créditos y crecimiento empresarial en la cooperativa Nuestra Señora del Rosario, agencia Huamachuco, 2018 - 2020 - Ramos Tumbajulca, Jenny Raquel (2021)
The general objective of this research was to establish the relationship between credit risk management and business growth in the Cooperativa Nuestra Señora del Rosario, Huamachuco Agency, period 2018-2020. Whose research problem was: What is the relationship between credit risk management and business growth in the Cooperativa Nuestra Señora del Rosario, Huamachuco Agency, period 2018-2020? The research design that was used was non-experimental, with a transectional correlational design, the population was made up of 1178 partners -clients of the Credit area, and the sample was 290, to whom the survey technique was applied, by means of the questionnaire. Among the main results are that both credit risk management and business growth qualify at a regular level, which means that the entity has weaknesses and strengths, highlighting the weaknesses in the collection policies and in the interest rates that cobra. Concluding that the risk management factors that are most closely related to the level of growth of the cooperative are the credit and collection policies, since through these indicators, the effectiveness of managing the credit granting process can be measured, which will allow to reduce the level of delinquency, and allow the growth of the cooperative.